2022
DOI: 10.1155/2022/7300303
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Carrying out Continuous Nursing Based on Mobile Platform on the Life of Children with Leukemia after Discharge from Hospital

Abstract: Objective. To analyze the effect of carrying out continuous nursing based on mobile platform on the life of children with leukemia after discharge. Methods. A total of 104 children diagnosed with leukemia admitted in Pediatric Internal Medicine, Hainan Provincial People’s Hospital, from September 2019 to August 2020 were randomly divided into two groups, observation group and control group, with 52 cases in each group. For the control group, routine follow-up was used for continuous nursing after discharge fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%